Measurement of electrostatic tip–sample interactions by time-domain Kelvin probe force microscopy - Ritz, Christian; Wagner, Tino; Stemmer, Andreas (Beilstein Journal of Nanotechnology, 2020)
Kelvin probe force microscopy is a scanning probe technique used to quantify the local electrostatic potential of a surface. In common implementations, the bias voltage between the tip and the sample is modulated. The resulting electrostatic force or force gradient is detected via lock-in techniques and canceled by adjusting the dc component of the tip–sample bias. This allows for an electrostatic characterization and simultaneously minimizes the electrostatic influence onto the topography measurement. However, a static contribution due to the bias modulation itself remains uncompensated, which can induce topographic height errors. Here, we demonstrate an alternative approach to find the surface potential without lock-in detection. Our method operates directly on the frequency-shift signal measured in frequency-modulated atomic force microscopy and continuously estimates the electrostatic influence due to the applied voltage modulation. This results in a continuous measurement of the local surface potential, the capacitance gradient, and the frequency shift induced by surface topography. In contrast to conventional techniques, the detection of the topography-induced frequency shift enables the compensation of all electrostatic influences, including the component arising from the bias modulation. This constitutes an important improvement over conventional techniques and paves the way for more reliable and accurate measurements of electrostatics and topography.
Keywords: atomic force microscopy (AFM); electrostatic height error; extended Kalman filter; Kelvin probe force microscopy (KFM); time domain

(untitled) - Weaver, J. M. R.; Abraham, D. W. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1991)

(untitled) - Nonnenmacher, M.; O’Boyle, M. P.; Wickramasinghe, H. K. (Appl. Phys. Lett., 1991)

(untitled) - Jacobs, H. O.; Knapp, H. F.; Stemmer, A. (Rev. Sci. Instrum., 1999)

(untitled) - Mesquida, P.; Knapp, H. F.; Stemmer, A. (Surf. Interface Anal., 2002)

(untitled) - Jacobs, H. O.; Whitesides, G. M. (Science, 2001)

(untitled) - Gysin, U.; Meyer, E.; Glatzel, T.; Günzburger, G.; Rossmann, H. R.; Jung, T. A.; Reshanov, S.; Schöner, A.; Bartolf, H. (Microelectron. Eng., 2016)

(untitled) - Könemann, F.; Vollmann, M.; Wagner, T.; Mohd Ghazali, N.; Yamaguchi, T.; Stemmer, A.; Ishibashi, K.; Gotsmann, B. (J. Phys. Chem. C, 2019)

(untitled) - Wagner, T.; Menges, F.; Riel, H.; Gotsmann, B.; Stemmer, A. (Beilstein J. Nanotechnol., 2018)

(untitled) - Söngen, H.; Rahe, P.; Neff, J. L.; Bechstein, R.; Ritala, J.; Foster, A. S.; Kühnle, A. (J. Appl. Phys., 2016)

Kelvin Probe Force Microscopy - Söngen, H.; Rahe, P.; Bechstein, R.; Kühnle, A. (Interpretation of KPFM Data with the Weight Function for Charges, 2018)

(untitled) - Sommerhalter, C.; Glatzel, T.; Matthes, T. W.; Jäger-Waldau, A.; Lux-Steiner, M. C. (Appl. Surf. Sci., 2000)

(untitled) - Kitamura, S.; Iwatsuki, M. (Appl. Phys. Lett., 1998)

(untitled) - Wagner, T.; Beyer, H.; Reissner, P.; Mensch, P.; Riel, H.; Gotsmann, B.; Stemmer, A. (Beilstein J. Nanotechnol., 2015)

(untitled) - Wagner, T.; Köhler, D.; Milde, P.; Eng, L. M. (Appl. Phys. Lett., 2013)

(untitled) - Lee, M.; Lee, W.; Prinz, F. B. (Nanotechnology, 2006)

(untitled) - Collins, L.; Kilpatrick, J. I.; Weber, S. A. L.; Tselev, A.; Vlassiouk, I. V.; Ivanov, I. N.; Jesse, S.; Kalinin, S. V.; Rodriguez, B. J. (Nanotechnology, 2013)

(untitled) - Sadewasser, S.; Lux-Steiner, M. C. (Phys. Rev. Lett., 2003)

(untitled) - Sadewasser, S.; Carl, P.; Glatzel, T.; Lux-Steiner, M. C. (Nanotechnology, 2004)

(untitled) - Ziegler, D.; Rychen, J.; Naujoks, N.; Stemmer, A. (Nanotechnology, 2007)

(untitled) - Ziegler, D.; Naujoks, N.; Stemmer, A. (Rev. Sci. Instrum., 2008)

(untitled) - Ziegler, D.; Stemmer, A. (Nanotechnology, 2011)

(untitled) - Kawai, S.; Sadeghi, A.; Feng, X.; Lifen, P.; Pawlak, R.; Glatzel, T.; Willand, A.; Orita, A.; Otera, J.; Goedecker, S.; Meyer, E. (ACS Nano, 2013)

(untitled) - Collins, L.; Belianinov, A.; Somnath, S.; Balke, N.; Kalinin, S. V.; Jesse, S. (Sci. Rep., 2016)

(untitled) - Gross, L.; Mohn, F.; Liljeroth, P.; Repp, J.; Giessibl, F. J.; Meyer, G. (Science, 2009)

(untitled) - Schumacher, Z.; Miyahara, Y.; Spielhofer, A.; Grutter, P. (Phys. Rev. Appl., 2016)

(untitled) - Melitz, W.; Shen, J.; Kummel, A. C.; Lee, S. (Surf. Sci. Rep., 2011)

Kelvin Probe Force Microscopy - Sadewasser, S. (Experimental technique and working modes, 2012)

(untitled) - Burke, S. A.; LeDue, J. M.; Miyahara, Y.; Topple, J. M.; Fostner, S.; Grütter, P. (Nanotechnology, 2009)

(untitled) - Lübbe, J.; Temmen, M.; Rode, S.; Rahe, P.; Kühnle, A.; Reichling, M. (Beilstein J. Nanotechnol., 2013)

Optimal State Estimation - Simon, D. (Wiley-Interscience, 2006)

(untitled) - Simon, D. (IET Control Theory Appl., 2010)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Huang, Y.; Sutter, E.; Shi, N. N.; Zheng, J.; Yang, T.; Englund, D.; Gao, H.-J.; Sutter, P. (ACS Nano, 2015)

(untitled) - Cao, P.; Xu, K.; Varghese, J. O.; Heath, J. R. (Nano Lett., 2011)

(untitled) - Kazakova, O.; Panchal, V.; Burnett, T. L. (Crystals, 2013)

(untitled) - Ziegler, D.; Gava, P.; Güttinger, J.; Molitor, F.; Wirtz, L.; Lazzeri, M.; Saitta, A. M.; Stemmer, A.; Mauri, F.; Stampfer, C. (Phys. Rev. B, 2011)